Performance evaluation of D2D communications in of LTE-A network - Hassan, Mona Bakri; Saeed, Rashid A.; Khalifa, Othman Omran; Sayed Ali, Elmustafa; Mokhtar, Rania A. (IEEE, 2023)
In LTE-Advanced, device-to-device (D2D) communication is a technology enables to increase the coverage and capacity coverage in metropolitan areas. Improvements in energy efficiency, throughput, latency, spectrum efficiency, and interference reduction have all been proposed. It is used in many domains, including applications, network traffic offloading, and public safety, and is recognized as one of the viable ways for the 5G wireless communications system. LTE advanced might perform worse in D2D communications because of multipath impact and delay dispersion. It is an essential and important element for the design of receivers in mobile communication systems. In this study, the spectrum efficiency, throughput, data rate, signal-to-interference-pulse-noise ratio, and latency of LTE-based D2D communications will be examined (SINR).